"IC-Lock Store" Sebagai Jembatan Keberlanjutan PKMT Menjadi Bisnis Dalam Upaya Kemandirian Mahasiswa - Syahidin, Nanang; Lestari, Puji; Rebono, Rebono; Habibah, Firstyarikha; Hartono, Sarwenda (Program Kreativitas Mahasiswa - Kewirausahaan, 2014)
Motor vehiclesare essential and numbers in Indonesia is increasing every year. However, the increase in motor vehicle growth was followed by an increase in the crime rate of motor vehicle theft. During the year 2013 in Central Java theft of a motor cases reached 4,616 cases. The theft case was triggered by a variety of factors including the vehicle that is note quipped with additional safety. Based on the above issues, we provide a solution in the form of motor vehicle safety accessories with light coding innovations. This safety device made from simple electronic and durable components. The purpose of this program is to help people get a motorcycle safety products are cheap and safe, and students can develop an entrepreneurial spiritthrough IC-Lock store. Preparation for developing IC-Lock products begins with the determination of the location of the business and preparation of raw materials to the end product can be marketed and used by the public. Currently, there are 2 types of IC Lock, namely 1 L type (1 lamp code) and 2 L type (2 lamp code). The number of IC-Lock products are sold as much as 911 pcs with a profit of Rp. 38,281,000.00for 10 months of the program. IC-Lock store has had a business entity with the name CV. INDOSAHADA. This effort will continue to be developed with a variety of innovations such as developing a product that is compatible with the car and add an alarm feature.Keywords : Sour-sop leaves, amplitude response, sensitivity, medical radiography